Three-dimensional composite copper foil for solid-state lithium battery and preparation method of three-dimensional composite copper foil
The three-dimensional composite copper foil addresses the weight and cost issues of solid-state lithium batteries by using a porous membrane layer with metallization layers to enhance lithium ion movement, reducing weight and manufacturing costs while increasing charging and discharging speed.
Patent Information
- Application Number
- CN202411494186.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-13
AI Technical Summary
Existing solid-state lithium batteries use heavy and costly copper foil as the negative electrode current collector, leading to high weight and manufacturing costs, and slow lithium ion movement due to the absence of holes in the copper foil, which reduces charging and discharging speed.
A three-dimensional composite copper foil is developed, comprising a support layer with metallization layers and conductive copper layers, utilizing a porous or fiber membrane layer with controlled porosity and metallization materials to enhance lithium ion movement and reduce copper usage.
The composite copper foil reduces the weight and manufacturing cost of solid-state lithium batteries while improving charging and discharging speed by allowing rapid lithium ion movement through the porous membrane and meeting current carrying and tensile strength requirements.
Smart Images

Figure CN119133465A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery production, and in particular to a three-dimensional composite copper foil for a solid lithium battery and a preparation method thereof. Background Art
[0002] Existing solid-state lithium batteries generally use copper foil as the negative electrode current collector. Since copper foil is generally solid copper, it is heavy, and the amount of copper material used is large and the cost is high, which leads to the heavy weight of solid-state lithium batteries and increases the manufacturing cost of solid-state lithium batteries. At the same time, during the charging and discharging process of solid-state lithium batteries, since there are no holes on the copper foil for lithium ions in the electrolyte to pass through, the speed at which lithium ions in the electrolyte move from one side of the copper foil to the other side of the copper foil will be relatively slow, reducing the charging and discharging speed of the solid-state lithium battery. Summary of the invention
[0003] In order to overcome the shortcomings of the prior art, the present invention provides a three-dimensional composite copper foil for a solid-state lithium battery and a preparation method thereof, which can reduce the weight of the solid-state lithium battery and reduce the manufacturing cost of the solid-state lithium battery, while increasing the charging and discharging speed of the solid-state lithium battery.
[0004] The technical solution adopted by the present invention to solve its technical problem is:
[0005] A first aspect of the present invention provides a three-dimensional composite copper foil for a solid-state lithium battery, comprising a support layer, wherein the support layer is a porous membrane layer or a fiber membrane layer, wherein a first metallization layer and a second metallization layer are respectively provided on both sides of the support layer, a third metallization layer is provided on a side of the first metallization layer away from the support layer, a fourth metallization layer is provided on a side of the second metallization layer away from the support layer, a first conductive copper layer is provided on a side of the third metallization layer away from the first metallization layer, and a second conductive copper layer is provided on a side of the fourth metallization layer away from the second metallization layer.
[0006] As a preferred technical solution, the porous membrane layer is a PET porous membrane layer, a PP porous membrane layer, a PI porous membrane layer or a PE porous membrane layer.
[0007] As a preferred technical solution, the fiber membrane layer is a PET fiber membrane layer, a PP fiber membrane layer, a PI fiber membrane layer or a PE fiber membrane layer.
[0008] As a preferred technical solution, the pores of the porous membrane layer or fiber membrane layer have a pore size of 0.05-500 μm and a porosity of 0.1%-80%.
[0009] As a preferred technical solution, the materials of the first metallization layer and the second metallization layer are both one or more combinations of cobalt, aluminum, nickel, cadmium, magnesium, lithium and manganese.
[0010] As a preferred technical solution, the third metallization layer and the fourth metallization layer are both made of copper or copper alloy.
[0011] As a preferred technical solution, the thickness of the support layer is 1-30 μm.
[0012] As a preferred technical solution, the thickness of the first metallization layer and the second metallization layer are both 5-100 nm, and the thickness of the third metallization layer and the fourth metallization layer are both 10-200 nm.
[0013] As a preferred technical solution, the thickness of the first conductive copper layer and the second conductive copper layer are both 500-2000 nm.
[0014] A second aspect of the present invention provides a method for preparing a three-dimensional composite copper foil for a solid-state lithium battery, comprising the following steps:
[0015] S1. Providing a support layer, wherein the support layer is a porous membrane layer or a fiber membrane layer;
[0016] S2, respectively disposing a first metallization layer and a second metallization layer on both sides of the support layer by magnetron sputtering, evaporation or chemical plating;
[0017] S3, disposing a third metallization layer on a side of the first metallization layer away from the support layer and disposing a fourth metallization layer on a side of the second metallization layer away from the support layer by magnetron sputtering, evaporation or chemical plating;
[0018] S4. Disposing a first conductive copper layer on a side of the third metallization layer away from the first metallization layer and a second conductive copper layer on a side of the fourth metallization layer away from the second metallization layer by electroplating or evaporation.
[0019] The beneficial effects of the present invention are as follows: the present invention can reduce the weight of the composite copper foil and the amount of copper material used by setting a support layer, which is a porous membrane layer or a fiber membrane layer, thereby reducing the weight of the solid-state lithium battery and the manufacturing cost of the solid-state lithium battery, and during the charging and discharging process of the solid-state lithium battery, the holes on the porous membrane layer or the holes on the fiber membrane layer can serve as channels for the movement of lithium ions in the electrolyte, so that the lithium ions in the electrolyte of the solid-state lithium battery can quickly move from one side of the composite copper foil to the other side of the composite copper foil, thereby improving the charging and discharging speed of the solid-state lithium battery, and by setting the first conductive copper layer and the second conductive copper layer, the current carrying performance requirements and tensile strength requirements of the composite copper foil can be met, thereby meeting the performance requirements of the solid-state lithium battery. In addition, the first metallization layer is provided to isolate the first conductive copper layer and the support layer, and the second metallization layer is provided to isolate the second conductive copper layer and the support layer, thereby protecting the support layer. During the high and low temperature cycle test of the solid-state lithium battery, the support layer can be prevented from being burned through, thereby improving the stability of the composite copper foil during the high and low temperature cycle test of the solid-state lithium battery. The third and fourth metallization layers can improve the adhesion between the first metallization layer and the first conductive copper layer, and the adhesion between the second metallization layer and the second conductive copper layer, thereby preventing the first conductive copper layer and the second conductive copper layer from falling off. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0021] Figure 1 It is a schematic structural diagram of a three-dimensional composite copper foil for a solid-state lithium battery provided by one embodiment of the present invention;
[0022] Figure 2 is based on Figure 1 The three-dimensional composite copper foil for solid-state lithium batteries shown is a schematic flow chart of a method for preparing the three-dimensional composite copper foil for solid-state lithium batteries. DETAILED DESCRIPTION
[0023] The following will clearly and completely describe the concept, specific structure and technical effects of the present invention in combination with the embodiments and drawings, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. In addition, all the connection / connection relationships involved in the patent do not refer to the direct connection of components, but refer to the formation of a better connection structure by adding or reducing connection accessories according to the specific implementation situation. The various technical features in the invention can be combined interchangeably without conflicting with each other.
[0024] Please refer to Figure 1 A three-dimensional composite copper foil for a solid lithium battery provided in one embodiment of the present invention includes a support layer 10, and the support layer 10 is a porous membrane layer or a fiber membrane layer. A first metallization layer 20 and a second metallization layer 30 are provided on both sides of the support layer 10, respectively. A third metallization layer 40 is provided on the side of the first metallization layer 20 away from the support layer 10. A fourth metallization layer 50 is provided on the side of the second metallization layer 30 away from the support layer 10. A first conductive copper layer 60 is provided on the side of the third metallization layer 40 away from the first metallization layer 20. A second conductive copper layer 70 is provided on the side of the fourth metallization layer 50 away from the second metallization layer 30.
[0025] Through the above structure, the composite copper foil of the present invention, the supporting layer 10 is a porous membrane layer or a fiber membrane layer, which plays a role in supporting the entire composite copper foil, has the characteristics of light weight, low cost, and good ductility, can reduce the weight of the composite copper foil and can reduce the amount of copper material, thereby reducing the weight of the solid-state lithium battery and the manufacturing cost of the solid-state lithium battery, and at the same time can improve the ductility of the composite copper foil, can avoid the solid-state lithium battery from being damaged or broken due to the expansion or contraction of the electrolyte during the charging and discharging process, and in the process of charging and discharging of the solid-state lithium battery, the holes on the porous membrane layer or the holes on the fiber membrane layer can serve as channels for the movement of lithium ions in the electrolyte, so that the lithium ions in the electrolyte of the solid-state lithium battery can quickly move from one side of the composite copper foil to the other side of the composite copper foil, thereby improving the charging and discharging speed of the solid-state lithium battery. The first conductive copper layer 60 and the second conductive copper layer 70 are provided, and have good conductivity, which can meet the current carrying performance requirements and tensile strength requirements of the composite copper foil, thereby meeting the performance requirements of the solid-state lithium battery. The first metallization layer 20 is provided to isolate the first conductive copper layer 60 from the support layer 10, and the second metallization layer 30 is provided to isolate the second conductive copper layer 70 from the support layer 10, thereby protecting the support layer 10. During the high and low temperature cycle test of the solid-state lithium battery, the support layer 10 can be prevented from being burned through, thereby improving the stability of the composite copper foil during the high and low temperature cycle test of the solid-state lithium battery. The third metallization layer 40 is provided to improve the adhesion between the first metallization layer 20 and the first conductive copper layer 60, and to prevent the first conductive copper layer 60 from falling off. The fourth metallization layer 50 is provided to improve the adhesion between the second metallization layer 30 and the second conductive copper layer 70, and to prevent the second conductive copper layer 70 from falling off.
[0026] In this embodiment, a first metallization layer 20 and a second metallization layer 30 are respectively provided on both sides of the support layer 10 by magnetron sputtering, evaporation or chemical plating, a third metallization layer 40 is provided on a side of the first metallization layer 20 away from the support layer 10 by magnetron sputtering, evaporation or chemical plating, a fourth metallization layer 50 is provided on a side of the second metallization layer 30 away from the support layer 10 by magnetron sputtering, evaporation or chemical plating, a first conductive copper layer 60 is provided on a side of the third metallization layer 40 away from the first metallization layer 20 by electroplating or evaporation, and a second conductive copper layer 70 is provided on a side of the fourth metallization layer 50 away from the second metallization layer 30 by electroplating or evaporation.
[0027] The porous membrane layer is a PET (Polyethylene terephthalate, polyethylene terephthalate plastic) porous membrane layer, a PP (Polypropylene, polypropylene) porous membrane layer, a PI (Polyimide, polyimide) porous membrane layer or a PE (Polyethylene, polyethylene) porous membrane layer. The density of the PET porous membrane layer, the PP porous membrane layer, the PI porous membrane layer, and the PE porous membrane layer is low, which can further reduce the weight of the composite copper foil, thereby further reducing the weight of the solid-state lithium battery, and is easy to manufacture.
[0028] The fiber membrane layer is a PET fiber membrane layer, a PP fiber membrane layer, a PI fiber membrane layer or a PE fiber membrane layer. The density of the PET fiber membrane layer, the PP fiber membrane layer, the PI fiber membrane layer and the PE fiber membrane layer is low, which can further reduce the weight of the composite copper foil, thereby further reducing the weight of the solid-state lithium battery and facilitating manufacturing.
[0029] The pores of the porous membrane layer or the fiber membrane layer have a pore size of 0.05-500 μm and a porosity of 0.1%-80%, which can ensure that lithium ions can pass through the pores, and when the first metallization layer 20 and the second metallization layer 30 are arranged on both sides of the support layer 10 by magnetron sputtering, evaporation or chemical plating, metal filling in the pores can be avoided.
[0030] The materials of the first metallization layer 20 and the second metallization layer 30 are one or more combinations of cobalt, aluminum, nickel, cadmium, magnesium, lithium and manganese. A dense isolation layer can be formed by using a variety of combinations of metals.
[0031] The third metallization layer 40 and the fourth metallization layer 50 are both made of copper or copper alloy, and the first conductive copper layer 60 and the second conductive copper layer 70 are both made of copper. The third metallization layer 40 and the fourth metallization layer 50 use copper or copper alloy. When the first conductive copper layer 60 is provided on the side of the third metallization layer 40 away from the first metallization layer 20 by electroplating or evaporation, and when the second conductive copper layer 70 is provided on the side of the fourth metallization layer 50 away from the second metallization layer 30 by electroplating or evaporation, the speed of generating the first conductive copper layer 60 and the second conductive copper layer 70 can be increased.
[0032] The thickness of the supporting layer 10 is 1-30 μm (micrometer), preferably 10 μm, the thickness of the first metallized layer 20 and the second metallized layer 30 are both 5-100 nm (nanometer), preferably 50 nm, the thickness of the third metallized layer 40 and the fourth metallized layer 50 are both 10-200 nm, preferably 100 nm, the thickness of the first conductive copper layer 60 and the second conductive copper layer 70 are both 500-2000 nm, preferably 1000 nm. With this thickness, the total thickness of the composite copper foil of the present invention is between 2.03-34.6 μm. The small thickness can further reduce the weight of the composite copper foil, thereby further reducing the weight of the solid-state lithium battery.
[0033] Please refer to Figure 2 Based on the above-mentioned solid-state lithium battery composite copper foil, the present invention also provides a method for preparing a solid-state lithium battery composite copper foil, comprising the following steps:
[0034] S1. Provide a support layer 10. The width and length of the support layer 10 can be set according to actual conditions. The thickness of the support layer 10 is 1-30 μm. The support layer 10 is a porous membrane layer or a fiber membrane layer. The porous membrane layer is a PET porous membrane layer, a PP porous membrane layer, a PI porous membrane layer or a PE porous membrane layer. The fiber membrane layer is a PET fiber membrane layer, a PP fiber membrane layer, a PI fiber membrane layer or a PE fiber membrane layer. The pores of the porous membrane layer or the fiber membrane layer have a pore size of 0.05-500 μm and a porosity of 0.1%-80%.
[0035] S2. A first metallization layer 20 and a second metallization layer 30 are respectively disposed on both sides of the support layer 10 by magnetron sputtering, evaporation or chemical plating. The materials of the first metallization layer 20 and the second metallization layer 30 are both one or more combinations of cobalt, aluminum, nickel, cadmium, magnesium, lithium and manganese. The thickness of the first metallization layer 20 and the second metallization layer 30 is 5-100 nm.
[0036] S3. A third metallization layer 40 is disposed on a side of the first metallization layer 20 away from the support layer 10 and a fourth metallization layer 50 is disposed on a side of the second metallization layer 30 away from the support layer 10 by magnetron sputtering, evaporation or chemical plating. The third metallization layer 40 and the fourth metallization layer 50 are both made of copper or copper alloy. The thickness of the third metallization layer 40 and the fourth metallization layer 50 is 10-200 nm.
[0037] S4. A first conductive copper layer 60 is disposed on a side of the third metallization layer 40 away from the first metallization layer 20 and a second conductive copper layer 70 is disposed on a side of the fourth metallization layer 50 away from the second metallization layer 30 by electroplating or evaporation. The first conductive copper layer 60 and the second conductive copper layer 70 are both made of copper, and the thickness of the first conductive copper layer 60 and the second conductive copper layer 70 are both 500-2000 nm.
[0038] The preparation method of the present invention has a simple process and is easy to manufacture. The prepared composite copper foil is light in weight and low in cost, thereby reducing the weight of the solid-state lithium battery and reducing the manufacturing cost of the solid-state lithium battery. At the same time, the charging and discharging speed of the solid-state lithium battery can be improved, greatly meeting the use requirements.
[0039] The above is a specific description of the preferred implementation of the present invention, but the invention is not limited to the embodiments. Those skilled in the art can make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A three-dimensional composite copper foil for solid-state lithium batteries, characterized in that: The invention comprises a supporting layer, wherein the supporting layer is a porous membrane layer or a fiber membrane layer, wherein a first metallization layer and a second metallization layer are respectively arranged on two sides of the supporting layer, a third metallization layer is arranged on a side of the first metallization layer away from the supporting layer, a fourth metallization layer is arranged on a side of the second metallization layer away from the supporting layer, a first conductive copper layer is arranged on a side of the third metallization layer away from the first metallization layer, and a second conductive copper layer is arranged on a side of the fourth metallization layer away from the second metallization layer.
2. The three-dimensional composite copper foil for solid-state lithium batteries according to claim 1, characterized in that: The porous membrane layer is a PET porous membrane layer, a PP porous membrane layer, a PI porous membrane layer or a PE porous membrane layer.
3. The three-dimensional composite copper foil for solid-state lithium batteries according to claim 1, characterized in that: The fiber membrane layer is a PET fiber membrane layer, a PP fiber membrane layer, a PI fiber membrane layer or a PE fiber membrane layer.
4. The three-dimensional composite copper foil for solid-state lithium batteries according to claim 1, characterized in that: The pores of the porous membrane layer or the fiber membrane layer have a pore size of 0.05-500 μm and a porosity of 0.1%-80%.
5. The three-dimensional composite copper foil for solid-state lithium batteries according to claim 1, characterized in that: The materials of the first metallization layer and the second metallization layer are one or more combinations of cobalt, aluminum, nickel, cadmium, magnesium, lithium and manganese.
6. The three-dimensional composite copper foil for solid-state lithium batteries according to claim 1, characterized in that: The third metallization layer and the fourth metallization layer are both made of copper or copper alloy.
7. The three-dimensional composite copper foil for solid-state lithium batteries according to claim 1, characterized in that: The thickness of the support layer is 1-30 μm.
8. The three-dimensional composite copper foil for solid-state lithium batteries according to claim 1, characterized in that: The thickness of the first metallization layer and the second metallization layer are both 5-100 nm, and the thickness of the third metallization layer and the fourth metallization layer are both 10-200 nm.
9. The three-dimensional composite copper foil for solid-state lithium batteries according to claim 1, characterized in that: The thickness of the first conductive copper layer and the second conductive copper layer are both 500-2000 nm.
10. A method for preparing a three-dimensional composite copper foil for a solid-state lithium battery, characterized in that: The following steps are involved: S1. Providing a support layer, wherein the support layer is a porous membrane layer or a fiber membrane layer; S2, respectively disposing a first metallization layer and a second metallization layer on both sides of the support layer by magnetron sputtering, evaporation or chemical plating; S3, disposing a third metallization layer on a side of the first metallization layer away from the support layer and disposing a fourth metallization layer on a side of the second metallization layer away from the support layer by magnetron sputtering, evaporation or chemical plating; S4. Disposing a first conductive copper layer on a side of the third metallization layer away from the first metallization layer and a second conductive copper layer on a side of the fourth metallization layer away from the second metallization layer by electroplating or evaporation.
